A versatile strategy towards non-covalent functionalization of graphene by surface-confined supramolecular self-assembly of Janus tectons - Du, Ping; Bléger, David; Charra, Fabrice; Bouchiat, Vincent; Kreher, David; Mathevet, Fabrice; Attias, André-Jean (Beilstein Journal of Nanotechnology, 2015)
Two-dimensional (2D), supramolecular self-assembly at surfaces is now well-mastered with several existing examples. However, one remaining challenge to enable future applications in nanoscience is to provide potential functionalities to the physisorbed adlayer. This work reviews a recently developed strategy that addresses this key issue by taking advantage of a new concept, Janus tecton materials. This is a versatile, molecular platform based on the design of three-dimensional (3D) building blocks consisting of two faces linked by a cyclophane-type pillar. One face is designed to steer 2D self-assembly onto C(sp2)-carbon-based flat surfaces, the other allowing for the desired functionality above the substrate with a well-controlled lateral order. In this way, it is possible to simultaneously obtain a regular, non-covalent paving as well as supramolecular functionalization of graphene, thus opening interesting perspectives for nanoscience applications.
Keywords: C(sp2)-based substrates; graphene; Janus tecton; liquid–solid interface; scanning tunnelling microscopy; supramolecular self-assembly